A flavin-dependent monooxgenase confers resistance to chlorantraniliprole in the diamondback moth, Plutella xylostella. (December 2019) - Mallott, Mark; Hamm, Sarah; Troczka, Bartlomiej J.; Randall, Emma; Pym, Adam; Grant, Charles; Baxter, Simon; Vogel, Heiko; Shelton, Anthony M.; Field, Linda M.; Williamson, Martin S.; Paine, Mark; et al.
Abstract: The diamondback moth, Plutella xylostella, is a damaging pest of cruciferous crops, and has evolved resistance to many of the insecticides used for control, including members of the diamide class. Previous work on the molecular basis of resistance to diamides has documented mutations in the target-site, the ryanodine receptor, in resistant populations of P. xylostella worldwide. In contrast the role of metabolic resistance to this insecticide class is significantly less clear. Here we show that overexpression of a flavin-dependent monooxgenase (FMO) confers resistance to the diamide chlorantraniliprole in P. xylostella . Transcriptome profiling of diamide resistant strains, with and without target-site resistance, revealed constitutive over-expression of several transcripts encoding detoxification enzymes compared to susceptible strains. Two of these, CYP6BG1, and PxFMO2 were particularly highly overexpressed (33, 000 and 14, 700-fold, respectively) in a resistant strain (HAW) lacking target-site resistance. After 17 generations without diamide selection the resistance of the HAW strain fell by 52-fold and the expression of PxFMO2 by > 1300-fold, however, the expression of CYP6BG1 declined by only 3-fold. Generation of transgenic Drosophila melanogaster expressing these genes demonstrated that PxFMO2, but not CYP6BG1, confers resistance in vivo . Overexpression of PxFMO2 in the HAW strain is associated with mutations, including a putative transposable element insertion, in the promoter of this gene. These enhance the expression of a reporter gene when expressed in a lepidopteran cell line suggesting they are, at least in part, responsible for the overexpression of PxFMO2 in the resistant strain. Our results provide new evidence that insect FMOs can be recruited to provide resistance to synthetic insecticides. Graphical abstract: Image 1 Highlights: Resistance to chlorantraniliprole in Plutella xylostella is associated with the overexpression of detoxification genes. Two transcripts encoding CYP6BG1 and PxFMO2 are overexpressed >14, 000-fold in a resistant strain from Hawaii (HAW). PxFMO2 but not CYP6BG1 confer resistance to chlorantranilprole when expressed in transgenic D. melanogaster. In the absence of selection the resistance of the HAW strain fell by 52-fold and the expression of PxFMO2 by > 1000-fold. Mutations (including a repetitive element insertion) in the PxFMO2 promoter of the HAW strain enhance expression.